Alternative feedstuffs for swine in Colombia: what are our options? - Agudelo, Jorge Hernán (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Both the increasing demand of grains for food and the recent ethanol crisis have an economic impact on swine producers in many countries, including Colombia. The continuous increase in grain and corn prices push swine nutritionists everywhere to search for alternative energy feedstuffs in order to provide adequate feed to pigs. Colombia, where a variety of crops are grown, lacks effective alternative feedstuffs to replace corn, which is widely used as the main energy ingredient in common animal diets. The major limitations presented by those crops or products and their derived materials are usually their high water or high fiber contents, or both, particularly in the way they are made available from agricultural production and the food industry.